Legal Liability of E-Commerce Site Against Sales of Counterfeit Trademarks Products - Rani, Marnia; Sibarani, Hos Arie Rhamadhan; Swastiwi, Anastasia Wiwik; Haryanti, Dewi (Universitas Medan Area, 2025)
This article examines the legal liability of e-commerce platforms for selling counterfeit trademark products in Indonesia. The problem focuses on the extent of responsibility e-commerce platforms hold under Indonesian trademark law, particularly Law Number 20 of 2016 on Marks and Geographical Indications and Law Number 28 of 2014 on Copyrights. A statutory approach is used as a theoretical reference to approach this problem. The data is collected by qualitatively analyzing relevant legislation and policies. The study results show that the Trademark Law in Indonesia has not regulated the sale of products using counterfeit brands in e-commerce. The Copyright Law in Indonesia only regulates that the manager of a trading place can be held accountable if a sale of products violates copyright. In contrast, the Trademark Law does not restrict this. So that confusion arises: can the organizer of an electronic system in online buying and selling be held civilly liable if their e-commerce site provides products using counterfeit brands.